De novo assembly, annotation and analysis of transcriptome sequences of callus culture from Aquilaria malaccensis Lam. - Siah, Chai Har (2015)
Aquilaria malaccensis is a major source of agarwood, a rare and highly priced wood product. Due to its high demand, it is endangered and listed in the Appendix II of Convention on International Trade in Endangered Species of Wild Fauna and Flora. Because of insufficient genomic and transcriptomic data available in public database for understanding the molecular basis of agarwood formation, the goal of this study was to obtain A. malaccensis expressed gene sequences using the transcriptome sequencing by next-generation sequencing (NGS). To obtain sufficient data from NGS sequencing, a high quality RNA sample is required. The RNA yield, purity, and integrity of six different extraction methods were compared. Conventional methods yielded RNA with good purity but the RNA integrity was poor. When using modified RNeasy Plant Mini kit, the highest yield was obtained while maintaining the integrity of RNA. This method was used to extract total RNA from callus samples and sent for transcriptome sequencing. Callus tissues were treated under stress condition by nutrient shortage of 1.1 μm 1- naphthaleneacetic acid (NAA), 2.2 μm 6-benzylaminopurine (BAP), and 15 g/L sucrose; collected during death phase when it producing brownish exudates and agarwood scent. Two cDNA libraries were constructed from mRNAs of untreated and treated callus tissues and sequenced using paired-end libraries on an Illumina HiSeq2000 platform. After filtering and trimming, a total of 200,062,275 and 166,544,202 clean reads were obtained for untreated and treated callus libraries, respectively. De novo assembly was carried out using SOAPdenovo-Trans and TGICL. A total of 231,594 unigenes were generated from the assembly. Assembled sequences were annotated using BLASTX against the NCBI non-redundant protein database where 41.5% unigenes showed significant alignment. The differential gene expression value between untreated and treated samples were calculated using DEGseq. A total of 14,029 genes were identified as differentially expressed. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) annotations were reported using BLAST2GO software. Out of the 107,593 unigenes that showed significant alignment with non-redundant protein database, 96,743 unigenes were successfully annotated with at least one GO term. The annotations were classified into the three main GO categories: biological processes (50.7%), molecular functions (24.0%) and cellular components (25.3%). A total of 144 KEGG pathways were identified from 46,076 unigenes. Enrichment analysis showed that the genes were enriched in the stress responses and sesquiterpene biosynthesis activity. This is the first comprehensive de novo transcriptome assembly and profiling for A. malaccensis. These transcriptome libraries provide valuable transcriptomic reference resource for future research.